The Image of Elizabeth I in Early Modern Spain - Fernández Rodríguez, Esther; Olid Guerrero, Eduardo (Book collections on Project MUSE., 2019)
"The Image of Elizabeth I in Early Modern Spain explores the fictionalized, historical, and visual representations of Elizabeth I and their impact on the Spanish collective imagination."--Provided by publisher